Erratum: M. Trizzino, L. Carnevali, S. De Felici & Paolo Audisio (2013) A revision of Hydraena species of the "Haenydra" lineage (Coleoptera, Hydraenidae). Zootaxa, 3607 (1), 001–173. - Trizzino, Marco; Carnevali, Lucilla; Felici, Stefano De; Audisio, Paolo (Zootaxa, 2013)
(Erratum)